2017
DOI: 10.1016/j.pec.2016.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of a question prompt list to increase patient active participation during interactions with black patients and their oncologists

Abstract: Objective Communication during racially-discordant interactions is often of poor quality and may contribute to racial treatment disparities. We evaluated an intervention designed to increase patient active participation and other communication-related outcomes during interactions between Black patients and non-Black oncologists. Methods Participants were 18 non-Black medical oncologists and 114 Black patients at two cancer hospitals in Detroit, Michigan, USA. Before a clinic visit to discuss treatment, patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
92
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(95 citation statements)
references
References 64 publications
(78 reference statements)
3
92
0
Order By: Relevance
“…The study used de-identified data from a larger randomized control trial testing an intervention to improve communication between Black cancer patients and non-Black oncologists (Eggly et al, 2017). It was conducted between April 2012 and December 2014 in outpatient clinics of two cancer hospitals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study used de-identified data from a larger randomized control trial testing an intervention to improve communication between Black cancer patients and non-Black oncologists (Eggly et al, 2017). It was conducted between April 2012 and December 2014 in outpatient clinics of two cancer hospitals.…”
Section: Methodsmentioning
confidence: 99%
“…In general, communication and information exchange between physicians and patients in these interactions are poorer than in racially concordant interactions (Eggly et al, 2017). These dynamics of racially discordant medical interactions have significant practical implications for Black cancer patients: Over 80% of Black patients’ interactions with oncologists are racially discordant (Hamel et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Study Data were taken from a larger National Cancer Institute‐funded study conducted from 2012 to 2014, designed to improve patient‐oncologist communication during racially discordant interactions in the outpatient clinics of two cancer hospitals in Detroit, Michigan, USA . Oncologists were eligible to participate if they treated patients with breast, colon or lung cancer.…”
Section: Methodsmentioning
confidence: 99%
“…Question prompt lists have been found to give English‐speaking patients an established means, and permission, to engage in their healthcare, and increase the number of questions they ask in oncology consultations . Question prompt lists have also been used to improve communication in interactions between health professionals and English‐speaking patients from different ethnic backgrounds . While QPLs have been shown to be of benefit in English‐speaking cohorts, patient preference regarding the method and timing of delivery has not yet been determined …”
Section: Question Prompt Listsmentioning
confidence: 99%
“…15,26 Question prompt lists have also been used to improve communication in interactions between health professionals and English-speaking patients from different ethnic backgrounds. 27 While QPLs have been shown to be of benefit in English-speaking cohorts, patient preference regarding the method and timing of delivery has not yet been determined. 15 Our research team previously developed and piloted a communication intervention package comprising consultation ARs and QPLs to improve care for Arabic, Greek, Mandarin, and Cantonese-speaking patients with cancer.…”
Section: Question Prompt Listsmentioning
confidence: 99%